Penjadwalan Kapasitas Produksi Roti menggunakan Metode Rough Cut Capacity Planning di UMKM Cita Rasa Gorontalo - Abdullah, Aizza Kirana; Lahay, Idham Halid; Uloli, Hendra (LPPM Universitas Pahlawan Tuanku Tambusai, 2024)
MSME Cita Rasa is a manufacturing industry in Gorontalo City. Fulfillment of consumer demand for the quantity and time of orders is closely related to the availability of raw materials, labor, machines, working time and other resources that support bread-making production. Therefore, it is necessary to calculate the scheduling of capacity requirements for bread products to see available capacity and actual capacity. The aim of this research is to create a bread production plan and determine the feasibility of bread production capacity at MSME Cita Rasa using the Rough Cut Capacity Planning method. RCCP is a method used to measure work station capacity so that it can be seen whether a production schedule requires overtime work hours or subcontracts. Based on the results obtained, from the production capacity feasibility test using RCCP, it can be seen that all work stations in the MSME Cita Rasa have a positive value, which means the capacity is feasible